Securitising public health emergencies: a qualitative examination of the origins of military intervention in Sierra Leone's Ebola Epidemic - Samuel T Boland; Susannah Mayhew (BMJ Publishing Group, 2023)
Introduction The 2013-2016 West Africa Ebola Epidemic remains the largest recorded Ebola outbreak. In response to the escalating number of cases in Sierra Leone in the summer and early autumn of 2014, the British Armed Forces and Republic of Sierra Leone Armed Forces intervened in support of the outbreak response. Among other contributions, the militaries established and subsequently helped to lead a national network of bespoke (and inherently militarised) coordination centres, from which almost all formal Ebola response operations were organised. Their contributions were therefore central to the outbreak response. However, the decision and process by which these actors first intervened is not well documented.Methods In order to examine the historical origin of the militaries' intervention, 110 semistructured qualitative interviews with key stakeholders at the international, national and subnational level were conducted and analysed.Results Military support to Sierra Leone's Ebola response was found to result from the advocacy and careful planning of a small number of individuals operating in Freetown, alongside closed-door negotiations occurring at the highest level of government in the UK.Conclusions This has important implications for understanding elite decision-making related to the militarisation of aid and the wider securitisation agenda.